Women and Shopping - An Empirical Study of Bangalore City - Murugaiah, V.; Vishvas, Radhika (Indian Journal of Marketing, 2008)
Shopping is seriously catching up the top position in the women's leisure time activity list in the metros. No longer shopping is a compulsory responsibility; rather it's a 'pleasure trip' with a whole range of activities involving browsing, window-shopping, entertainment and excitement. For women, shopping has emerged as a perfect tailor made activity that suits their feminine role. Shopping has given them an opportunity for social expression, knowledge enhancement, skill development, confidence, and decision making role at the household level. As Sam Walton has revolutionized "Walmartization" in retailing, women are on their way to make "Womenization of shopping" as consumers. Today, women as a successful business executive of the home are spanning their decisions from pin to pictures for their family with pleasure. It is their seriousness and experiential shopping behavior that's making them an expert shopper. Retailers must en-cash this opportunity by concentrating and tailoring their strategies to suit and satisfy these "spending engines" that are going to drive the economies of the world in the coming days.